The development of a broadcast mass screening test of hearing - Satyendra Kumar (Journal of All India Institute of Speech and Hearing)
It was felt that no suitable hearing screening test was available, which could be made use of in screening the whole population of India, with the available personnel equipment and the other resources at hand.